Malaysian Community in New Zealand: Assimilation and Cultural Identity - Harun, Yaakob (Jurnal Peradaban Melayu, 2010)
This paper gives a brief profile of Malaysian community in New Zealand. Specific reference is made to the Malaysian community residing in the capital city of Wellington. The discussion falls under the following sub-topics: population structure and size, occupations and economic activities, student profiles, and assimilation process and cultural identity.